OC-154 Inter-observer agreement for manometry classification of individual swallows and diagnoses using high-resolution manometry (HRM) with esophageal pressure topography (EPT): results of high participation web-based studies by the HRM working group. (28th May 2012) - Fox, M R; Pandolfino, J; Jafari, J; Menne, D
Abstract : Introduction: Recently the HRM Working Group presented a classification system for esophageal motility disorders using HRM/EPT (Pandolfino, NGM 2009). This study reports inter-observer agreement for classification of individual HRM/EPT water swallows (study A) and diagnoses based on 10 swallows (study B) using this system. Methods: All registered members of the hrmconsensus.org website were invited to take part. Institution and experience with HRM were recorded. A sample of 147 individual swallows (study A) and 40 diagnostic studies (study B) was reviewed and classified using a drop down menu that utilised the published system. The on-line platform provided a generic EPT format with fixed pressure scale and time base. Contours facilitated analysis of intra-bolus and contractile pressure; however no data summary was provided. The sequence of swallows was fixed for each user, but randomised between users to avoid sequence bias. Users were blinded to other participant's entries. During the study users were free to reclassify and post comments; however, once completed classifications could not be changed. Results: (A) All 147 individual swallows were assessed by 18 users. High levels of agreement (≤2/18 dissenters) were present for normal peristalsis and achalasia but lower levels for peristaltic and intra-bolus pressure (IBP) abnormalities. (B) All 40 diagnostic studies were assessed by 36 users. Overall inter-observer agreement was fair (κ 0.42) being higher (κ>0.5) for aperistalsis and achalasia, and lower (κ<0.4) for peristaltic abnormalities. Users with >400 HRM/EPT studies showed somewhat better agreement (n=9; κ 0.46) and agreement was good for users in the US institution that developed the classification system (n=4; κ 0.57). Analysis of comments revealed that disagreements in both studies were not random but due to (1) multiple abnormalities in single swallows (2) limited functionality of on-line software/lack of a data summary that confounded user's ability to distinguish closely related diagnoses, especially those that depend on precise pressure measurement. Conclusion: This is the largest assessment of inter-observer agreement performed for manometric studies. Overall inter-observer agreement for HRM/EPT of individual swallows and diagnostic studies was moderate, increasing with experience of this technology and the classification system. Analysis of swallows with low agreement indicate that "pattern recognition" of HRM/EPT was not adequate and highlighted the value of objective metrics in diagnosis of esophageal dysmotility. Competing interests: M Fox consultant for: given imaging, paid instructor for: Sandhill MMS, J Pandolfino: None declared, J Jafari: None declared, D Menne: None declared.